Perancangan Keamanan Informasi pada Sistem Persuratan Berbasis Web Menggunakan Autentikasi dan Middleware - Panggah Widiandana; Muhammad Hafidz Amali; Adhitya Admaja; Maulana Raka Saputra (Bulletin of Computer Science Research, 2026)
The management of digital correspondence through web-based systems has improved administrative efficiency, but on the other hand, it introduces new vulnerabilities to cyber threats. Information security is a crucial aspect in the development of web-based mailing systems because this system manages incoming mail, outgoing mail, and official documents that are highly sensitive. Without a good security mechanism, the system has the potential to experience unauthorized access, data manipulation, and information leaks. Therefore, this study aims to design an information security mechanism through the application of authentication (auth) and middleware as system access controllers. The research method used is a system design method that includes security requirement analysis, Access Control Matrix modeling, routing interceptor architecture design, and Black-box authorization testing. In its application, authentication is used to ensure user identity before accessing the system, while middleware serves as a security layer to restrict access based on user roles. The design results show that the application of auth and middleware can improve access control, maintain data confidentiality, and strengthen information security in web-based mailing systems. The main contribution of this research is the provision of an integrated Role-Based Access Control (RBAC) layered information security model that can be adopted by various institutions to prevent privilege escalation and data manipulation in internal administration systems.